(untitled) (Research, Society and Development, 2020)
Objective: To present scientific evidence based on a systematic literature review (PRISMA) in relation to telehealth care in children with speech apraxia in childhood in order to answer the following research question: How effective is telehealth in children with speech apraxia in childhood. Methodology: For the selection of studies, the combination based on the Medical Subject Heading Terms (MeSH) was used: [(telehealth) OR (telepractice) OR (telerehabilitation) OR (teletherapy) OR (apraxia childhood speech) OR (dyspraxia) AND (child OR pediatrician)]. The Medline (Pubmed), LILACS, SciELO and BIREME databases were used. The search period for the articles covered the last 5 years (2015 to 2020). The designs of the selected studies were descriptive, cross-sectional, cohort and case study, which were related to the research objective. After reading the articles in full, identification data and methods were extracted from the articles for further analysis. Results: 969 articles were retrieved, after the exclusion phase, seven articles initially met the inclusion criteria, and one study answered the guiding question. Conclusion: There are promising indications of the efficacy of telehealth treatment in patients diagnosed with Child Speech Apraxia (AFI). However, it is important to emphasize that the results are still considered incipient, thus requiring an extension of the studies, with methodologies of randomized interventions, seeking to analyze the effectiveness of telehealth for these patients.